Tools for improving the efficiency of durum wheat selection under Mediterranean conditions - Royo C.; Aparicio N.; Villegas D.; García del Moral L.F.; Casadesús J.; Araus J.L. (Durum wheat improvement in the Mediterranean region: New challenges, 2000)
Future challenges of increasing productivity and quality in durum wheat will only be met by close co-operation of multidisciplinary teams who are able to incorporate new technologies. This work briefly reviews the benefits of the use of morphophysiological traits as selection criteria in breeding programmes, and the reasons for the lack of success in their use in the past. The need for collaborative work between physiologists and plant breeders in order to define and to validate traits for indirect selection is stressed. Furthermore, the paper deals with some of the most promising morphophysiological traits that have been recommended for improving selection efficiency in empirical breeding programmes. The concern of early vigor and plant biomass on grain yield is analysed, and methodologies for selecting for these traits, such as spectral reflectance measurements, are examined. Some issues related to the usefulness of other tools such as carbon isotope discrimination, canopy temperature, chlorophyll content and chlorophyll fluorescence are also considered.
Seminar on Durum Wheat Improvement in the Mediterranean Region: New Challenges, 2000/04/12-14, Zaragoza (Spain)